Coordenação e controle no modelo de gestão da estratégia de Minas Gerais: estudos de caso do Programa Descomplicar e do Projeto Caminhos de Minas - Oliveira, Júlia Torquato (2015)
The State Reforms movements observed at the end of the twentieth century, known as New Public Management – NPM, introduced a new dynamic in public administration, focused on results measurement, establishing relevant issues such as quality of provided services, satisfaction of user citizen, accountability and transparency. This paper, which aims to analyze the coordination and control instruments of strategy management model adopted by Minas Gerais’ State, initiates on that context and uses the theme of organizations power as theoretical background for description and explanation of interactions established between the main stakeholders of the program Descomplicar - Minas Inova and project Caminhos de Minas. This analysis verifies that the power does not manifest uniformly in the State Operating Systems, wherein the program and project studied are situated. While observing an especially political character in the relations stablished between the actors of Transportation System and Public Works, there is a technical character in the relations of Planning and Management System stakeholders. Even so, it appears that the coordination and control instruments do not apply accordingly to the original prescription for the functioning of the strategy management model in any of the analyzed initiatives. The observed weakening of coordination and control’s process and the loss of legitimacy of the Núcleo Central de Gestão Estratégica de Projetos e do Desempenho Institucional – NCGERAES to influence the allocation of resources from credit operations, relates to the pulverization of decision-makers instances observed in the context of 2011-2014 mandate of the government of Minas Gerais, resulting from the arrangement of coalitions established to ensure the governance conditions. Therefore, to strengthen coordination and control issues, it is suggested the revision of the budget decisions spray scenario towards the empowerment of NCGERAES, as the technical instance responsible for the strategic portfolio budgetary control. It is also recommended realigning the strategy management tools and redefining the priority deliveries as well as their monitoring format, focusing on the citizen.